Analisi Proses Pembuatan Shock Bracket Suspensi Bp-018 Dipt Karya Paduyasa - Abdul Syarif; Agus Wibowo (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to analyze problems in the manufacturing process of the BP-018 suspension shock bracket in order to improve production time efficiency. The shock is a tubular metal component that serves as a main part of the suspension bracket product. The production process of the shock bracket consists of several stages, including raw material cutting, first, second, and third-stage pressing, welding, grinding, and turning. The large number of processing stages required to produce a single shock bracket results in relatively long production time. Therefore, a production process analysis is necessary to identify opportunities for improvement and process optimization to increase time efficiency without reducing product quality. Keywords: production time efficiency, BP-018 suspension shock bracket, production process, metal manufacturing, process analysis and optimization Abstrak Penelitian ini bertujuan untuk menganalisis permasalahan pada proses pembuatan shock bracket suspensi BP-018 guna meningkatkan efisiensi waktu produksi. Shock merupakan komponen berbentuk tabung yang menjadi bagian utama dalam produk bracket suspensi. Proses produksi shock bracket terdiri dari beberapa tahapan, yaitu pemotongan bahan baku, pengepresan tahap 1, 2, dan 3, pengelasan, penggerindaan, serta pembubutan. Banyaknya tahapan proses dalam pembuatan satu produk shock bracket menyebabkan waktu produksi menjadi relatif lama. Oleh karena itu, diperlukan analisis proses produksi untuk mengidentifikasi peluang perbaikan dan optimasi guna meningkatkan efisiensi waktu tanpa mengurangi kualitas produk. Kata kunci: efisiensi waktu produksi, shock bracket suspensi BP-018, proses produksi, manufaktur logam, analisis dan optimasi proses